The liar - Roberts, Nora frey50 (New York G.P. Putnam's sons, 2015)
Devastated to learn that her unfaithful husband had actually married her using an alias, Shelby returns with her young daughter to her Tennessee hometown and pursues a new relationship before her husband's past poses dangerous threats.
Keywords: Fiction / Romance / Suspense; Fiction / Romance / General; Fiction / Romance / Contemporary; Single mothers; Attempted murder; Man-woman relationships; Man-woman relationships; Romantic suspense fiction; Fiction